2019
DOI: 10.1038/s41598-019-42659-z
|View full text |Cite
|
Sign up to set email alerts
|

Citrate synthase from Synechocystis is a distinct class of bacterial citrate synthase

Abstract: Citrate synthase (CS, EC 2.3.3.1) catalyses the initial reaction of the tricarboxylic acid (TCA) cycle. Although CSs from heterotrophic bacteria have been extensively studied, cyanobacterial CSs are not well-understood. Cyanobacteria can produce various metabolites from carbon dioxide. Synechocystis sp. PCC 6803 ( Synechocystis 6803) is a cyanobacterium used to synthesize metabolites through metabolic engineering techniques. The production of acetyl-CoA-derived met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…In contrast with many heterotrophic bacteria, Synechocystis citrate synthase (GltA) was shown only to catalyse generation of citrate, not its cleavage. Synechocystis GltA has a lower substrate affinity and turnover rate than the E. coli homologue, is not inhibited by ATP and NADH, but is inhibited by phosphoenolpyruvate [55].…”
Section: The Tricarboxylic Acid Cyclementioning
confidence: 97%
See 1 more Smart Citation
“…In contrast with many heterotrophic bacteria, Synechocystis citrate synthase (GltA) was shown only to catalyse generation of citrate, not its cleavage. Synechocystis GltA has a lower substrate affinity and turnover rate than the E. coli homologue, is not inhibited by ATP and NADH, but is inhibited by phosphoenolpyruvate [55].…”
Section: The Tricarboxylic Acid Cyclementioning
confidence: 97%
“…Synechocystis also encodes a succinyl-CoA synthetase complex (SucC/SucD), which probably catalyses the reversible conversion of succinate into succinyl-CoA in cyanobacteria [54], required for biosynthesis of methionine and lysine. Several recent papers have investigated the enzymatic properties of TCA enzymes conserved between cyanobacteria and heterotrophic bacteria [55][56][57]. In contrast with many heterotrophic bacteria, Synechocystis citrate synthase (GltA) was shown only to catalyse generation of citrate, not its cleavage.…”
Section: The Tricarboxylic Acid Cyclementioning
confidence: 99%
“…Additional effectors of Sy FumC enzymatic activity were examined under conditions of substrate saturation. We selected 11 effectors which regulate the activities of enzymes in the TCA cycle and pyruvate metabolism in this cyanobacterium 37,41 . Among the 11 effectors tested, Co 2+ and Zn 2+ decreased Sy FumC activity towards fumarate and l- malate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the regulation by metabolites and metals was not conserved among fumarases. Three TCA cycle enzymes ( Sy MDH, isocitrate dehydrogenase, and citrate synthase) in Synechocystis 6803 are regulated by divalent cations, particularly Mg 2+ 41,58,63 . Sy FumC was severely inhibited by Zn 2+ , not by Mg 2+ , indicating the different regulatory manner of enzymatic activities in the TCA cycle in this cyanobacterium.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the relative flux into the TCA cycle of cyanobacteria changes in dependence from growth conditions, for example the availability of inorganic carbon or nitrogen ( Schwarz et al, 2013a ). Recently, it has been reported that citrate synthase of the Synechocystis 6803 TCA cycle is highly regulated and that the TCA cycle intermediate citrate regulates the activity of the oxidative pentose-phosphate (OPP) pathway ( Ito et al, 2019 ; Ito and Osanai, 2020 ).…”
Section: Introductionmentioning
confidence: 99%